Effect of Government Regulations on Factors Hindering Financing of Small Scale Water Investments in Kenya - Kimani, Maina E. (Jomo Kenyatta University of Agriculture and Technology, 2015)
In Kenya, most water utilities have been publicly owned and managed. These utility firms have thus been getting financial support from the government in form of subsidies in addition to the revenue they generate internally. However there has been low level of investment in peri-urban areas by both public and private players creating an investment opportunity. Nevertheless this opportunity is not taken up by small scale water investors hence water scarcity. Many people in these areas do not have access to basic water. The general objective of the study was to determine the effect of government regulations on factors hindering financing of small scale water investments in Kenya. Specific objective of the study was to determine whether cost recovery, investor‘s perceived risk, access to capital and return on investments affect financing of small scale water investments in peri-urban areas in Nairobi Kenya. The study adopted cross-sectional survey research design. A two stage sampling technique was used to obtain a sample population of 150 Small Scale Water Service Providers (SSWPs). The study utilized self-administered semi-structured questionnaire and content analysis for collecting data. Structural Equation Modelling (SEM) and Moderated Multiple Regression (MMR) analysis was used to analyse the relationship between predictor variables and financing of small scale water investments. The findings of the study indicated that government regulation moderates the relationship between predictor variables and financing of small scale water investments. It was recommended that cost recovery should be improved, investor‘s risks should be mitigated and capital should be made available. In order to improve return on investments of small scale water investments, the government should enhance tariff reviews. The results of the study will contribute to greater understanding of various financial constraints that small scale water investors go through in trying to make water accessible to peri-urban population.
A thesis Submitted in Partial Fulfilment for the Degree of Doctor of Philosophy in Business Administration in the Jomo Kenyatta University of Agriculture and Technology